Comparison of soil and water pollution concentration determine using atomic absorption spectrophotometry (AAS) and x-ray fluorescence radioisotope (XRF) techniques - Umi Hani Amir (School of Environmental Engineering, University Malaysia Perlis, 2013)
Concentration of heavy metals in polluted soil and water in the closed dumping site at Kg. Wai, Kuala Perlis and oxidation pond at Wang Ulu, Kangar were determined using XRF and AAS techniques. Materials used were from contaminated soil and water which contained heavy metal.